2005
DOI: 10.1209/epl/i2005-10162-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of long-ranged and short-ranged forces in confined near-critical polymeric liquids

Abstract: The relative importance of long-and short-ranged forces on the thermal fluctuations at polymer interfaces was investigated with neutron reflection. Polyolefin blends were synthesised to create polymer pairs with a tuned interaction parameter, allowing the exploration of situations from near criticality to strongly immiscible cases in thin-film systems. We have observed for the polymer interfacial width, a transition from a region where long-ranged forces dominate, at higher degree of incompatibility, to a regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 17 publications
4
14
0
2
Order By: Relevance
“…We find several studies reported on the interfacial properties in terms of interdiffusion at the interface, [22][23][24][25][26] interfacial tension, [27][28][29][30] and interface width, 21,[31][32][33][34] and so forth in polymer blends. The magnitude and behavior of interface width with varying molecular weight, temperature, and film thickness have also been studied using the small angle neutron scattering, neutron reflectometry, 27,28,[33][34][35] small angle X-ray scattering, differential scanning calorimetry (DSC), 26 transmission electron microscopy, 30 and so forth with varying success.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…We find several studies reported on the interfacial properties in terms of interdiffusion at the interface, [22][23][24][25][26] interfacial tension, [27][28][29][30] and interface width, 21,[31][32][33][34] and so forth in polymer blends. The magnitude and behavior of interface width with varying molecular weight, temperature, and film thickness have also been studied using the small angle neutron scattering, neutron reflectometry, 27,28,[33][34][35] small angle X-ray scattering, differential scanning calorimetry (DSC), 26 transmission electron microscopy, 30 and so forth with varying success.…”
Section: Introductionmentioning
confidence: 91%
“…The magnitude and behavior of interface width with varying molecular weight, temperature, and film thickness have also been studied using the small angle neutron scattering, neutron reflectometry, 27,28,[33][34][35] small angle X-ray scattering, differential scanning calorimetry (DSC), 26 transmission electron microscopy, 30 and so forth with varying success. Schnell et al 5 had studied interfaces in blends of polystyrene with either poly (p-methylstyrene) or a statistical copolymer poly(styrene-co-pbromostyrene) using neutron reflection method.…”
Section: Introductionmentioning
confidence: 99%
“…This system has been studied intensely in experiments [137][138][139][140][141][142][143]. By mixing random copolymers of ethylene and ethyl-ethylene with two different, but very well defined copolymer ratios, Carelli et al [137,143] were able to tune the Flory-Huggins parameter very finely and study interfacial properties in a wide range of χ N between the weak segregation limit and the strong segregation limit. Figure 3.7 compares the results for the interfacial width and compares them with the mean-field prediction for the weak segregation limit, the strong segregation limit, and the full numerical result.…”
Section: An Application: Interfaces In Binary Blendsmentioning
confidence: 99%
“…On peut donc varier la miscibilité du système en changeant le ratio x dans la composition du polymère. Le choix de ce copolymère vient donc du fait qu'on peut facilement sélectionner la miscibilité des deux couches, grâce au paramètre d'interaction [25][26][27]. La T g (température de transition vitreuse du polymère) est d'environ −61 • C. Après la préparation, les échantillons sont donc conservés à une température de −80…”
Section: Choix Du Système De Polymèresunclassified
“…De plus, quand le degré d'immiscibilité décroît, l'interface devient plus large, et la dépendance avec Pour le système avec N = 31, une régression des points donne une dépendance logarithmique de la largeur de l'interface en fonction de l'épaisseur du film comme prédit pour les forces à longue portée tandis que pour N = 4.1 il y a une dépendance de la rugosité de l'interface en fonction de la racine carrée de l'épaisseur (avec éventuellement une interface intrinsèque réduite) comme prédit pour le cas des forces à courte portée [26,42,43].…”
Section: Systèmes Confinésunclassified